Symmetry breaking of highly symmetrical nanoclusters for triggering highly optical activity - Xiao Wei; Hao Li; Honglei Shen; Chuanjun Zhou; Shuxin Wang; Xi Kang; Manzhou Zhu (Fundamental Research, 2024)
Developing new approaches to fulfill the enantioseparation of nanocluster racemates and construct cluster-based nanomaterials with optical activity remains highly desired in cluster science, because it is an essential prerequisite for fundamental research and extensive applications of these nanomaterials. We herein propose a strategy termed “active-site exposing and partly re-protecting” to trigger the symmetry breaking of highly symmetrical nanoclusters and to render cluster crystals optically active. The vertex PPh3 of the symmetrical Ag29(SSR)12(PPh3)4 (SSR = 1, 3-benzenedithiol) nanocluster was firstly dissociated in the presence of counterions with large steric hindrance, and then the exposed Ag active sites of the obtained Ag29(SSR)12 nanocluster were partly re-protected by Ag+, yielding an Ag29(SSR)12-Ag2 nanocluster with a symmetry-breaking construction. Ag29(SSR)12-Ag2 followed a chiral crystallization mode, and its crystal displayed strong optical activity, derived from CD and CPL characterizations. Overall, this work presents a new approach (i.e., active-site exposing and partly re-protecting) for the symmetry breaking of highly symmetrical nanoclusters, the enantioseparation of nanocluster racemates, and the achievement of highly optical activity.